Petrogenesis of the Heyu Megaporphyritic Coarse-grained Monzogranite in the Baimiaogou Area, Western Henan: Petrological Evidence - Zhou, Xinhang (International Journal of Natural Resources and Environmental Studies, 2026)
The Heyu megaporphyritic coarse-grained monzogranite, located in the East Qinling area at the southern margin of the North China Craton, shows a distinctive sub-porphyritic texture and complex mineral assemblages that record the processes of magma formation and emplacement. Field investigations, petrography, and in-situ laser Raman spectroscopy reveal the micro-crystallization characteristics and fluid metasomatic sequences of the primary mineral phases. Early-crystallized plagioclase forms a rigid crystal framework (65% to 70% by volume) that records multiple stages of patchy albitization, K-feldspathization, and silicification. Mafic minerals (hornblende and biotite) and accessory phases (apatite, sphene, zircon, and magnetite) fill intergranular fractures within the felsic framework. These textures suggest precipitation from late-stage volatile-rich hydrothermal fluids rather than normal fractional crystallization. Petrographic evidence defines three dynamic stages of pluton evolution: early crystallization and cold storage of the crystal mush, deep fluid injection and mush reactivation, and magma emplacement with late-stage fluid precipitation. The large-scale influx of deep alkali-rich and volatile-rich supercritical fluids causes intense fluid-rock interaction, significantly reducing the rheological viscosity of the crystal mush. This viscosity reduction is the key mechanism to overcome the rheological barrier of high-silica magmas and facilitate final emplacement.